Collagen/kerateine multi-protein hydrogels as a thermally stable extracellular matrix for 3D in vitro models. (1st January 2021) - Zuniga, Kameel; Gadde, Manasa; Scheftel, Jacob; Senecal, Kris; Cressman, Erik; Van Dyke, Mark; Rylander, Marissa Nichole
Abstract: Objective: To determine whether the addition of kerateine (reduced keratin) in rat tail collagen type I hydrogels increases thermal stability and changes material properties and supports cell growth for use in cellular hyperthermia studies for tumor treatment. Methods: Collagen type I extracted from rat tail tendon was combined with kerateine extracted from human hair fibers. Thermal, mechanical, and biocompatibility properties and cell behavior was assessed and compared to 100% collagen type I hydrogels to demonstrate their utility as a tissue model for 3D in vitro testing. Results: A combination (i.e., containing both collagen 'C/KNT') hydrogel was more thermally stable than pure collagen hydrogels and resisted thermal degradation when incubated at a hyperthermic temperature of 47°C for heating durations up to 60 min with a higher melting temperature measured by DSC. An increase in the storage modulus was only observed with an increased collagen concentration rather than an increased KTN concentration; however, a change in ECM structure was observed with greater fiber alignment and width with an increase in KTN concentration. The C/KTN hydrogels, specifically 50/50 C/KTN hydrogels, also supported the growth and of fibroblasts and MDA-MB-231 breast cancer cells similar to those seeded in 100% collagen hydrogels. Conclusion: This multi-protein C/KTN hydrogel shows promise for future studies involving thermal stress studies without compromising the 3D ECM environment or cell growth.